Pengaruh Store Atmosphere, Desain Produk dan Harga Terhadap Keputusan Pembelian di Larissa Gallery & Workshop Pekalongan - Yauar Yoga Anggoro; Handoyo Djoko Waluyo (Universitas Diponegoro, 2017)
The existence of a batik shop business competition getting tougher in the city of Pekalongan, indirectly provide great challenges for the retail business to enhance purchase decisions. Purchase decision is the goal that must be achieved by each company. To achieve that goal, the shop batik Larissa need to pay attention to any matters that may affect the purchasing decision. This study examines the purchase decisions of Larissa Gallery & Workshop Pekalongan, relation to store atmosphere, product design and pricing.The purpose of this research is to know the influence of store atmosphere, product design and price of purchase at Larissa Gallery & Workshop Pekalongan. This research type is explanatory research with 100 respondents were taken by using a purposive sampling method and sampling of incidental. In this study, assisted by computer programs to process data that is SPSS version 23.0.The results showed that store atmosphere have influence on purchasing decisions with correlation coefficient 0.581, and the determination of the coefficient 33.8%, product design has an impact on purchasing decisions with a coefficient of correlation of 0.395, and the determination of the coefficient 15.6%, and prices have an impact on purchasing decisions with a coefficient of correlation of 0.287, and the determination of the coefficient 8.2%. Store atmosphere, product design and price collectively have an impact on purchasing decisions with the equation Y = -1.874 + 0.186 X1+0.132 X2+0.128 X3.The conclusion of this research is store atmosphere, product design and price influence to purchasing decision. The suggestions in this research is to improve the performance of its employees to be more interactive in serving the consumers who come, as well as improve the convenience of the shop atmosphere, then the company should be able to make design make-up of batik models and motifs that will be selling company, Up design model and interesting batik motifs will increase the appetite of batik product design expected by consumers, as well as the company in the sense of need to pay attention to several factors in terms of pricing to match the quality of the product in get it.